Psychometric Evaluation of the Japanese Version of the Posttraumatic Stress Disorder Checklist in Community Dwellers Following the Fukushima Daiichi Nuclear Power Plant Incident - Hajime Iwasa; Yuriko Suzuki; Tetsuya Shiga; Masaharu Maeda; Hirooki Yabe; Seiji Yasumura (SAGE Open, 2016)
We investigated the psychometric properties of the Japanese version of the Posttraumatic Stress Disorder Checklist–Stressor Specific Version (PCL-S) using baseline data from the Fukushima Health Management Survey. A total of 26,332 men and 33,516 women aged 16 and above participated in this study. Participants lived in the Fukushima evacuation zone in Japan and experienced the Great East Japan Earthquake and nuclear power plant (NPP) incident. The PCL-S was used to assess participants’ posttraumatic stress disorder (PTSD) symptoms. In addition, we described participants and tested the validity of the PCL-S by administering the Kessler Six-item Screening Scale for Psychological Distress (K6) and assessing education; employment; self-rated health; sleep satisfaction; experiencing the earthquake, tsunami, and NPP incident; and bereavement as a result of the disaster. PCL-S scores exhibited a positively skewed, slightly leptokurtic distribution. Confirmatory factor analysis revealed that the five-factor model was a better fit than were the three- or four-factor models. The PCL-S and its subscales had high Cronbach’s alpha coefficients. The PCL-S scores had weak-to-moderate correlations with history of mental illness, bereavement, experiencing the tsunami, experiencing the NPP incident, self-rated health, and sleep satisfaction, as well as a strong correlation with psychological distress. There were significant gender and age differences in PCL-S scores. Overall, this study confirmed the psychometric properties of the PCL-S, including the score distribution, factor structure, reliability, validity, and gender and age differences. Thus, the Japanese version of the PCL-S would be a useful instrument for assessing the PTSD symptoms of community dwellers who have experienced traumatic events.